Order and Architectural Beauty as Preconditions for Tourism Destination Competitiveness - Ahmad Wahidiyat Haedar (Universitas Negeri Makassar, 2023)
Order and architectural beauty are preconditions or the basis for the competitiveness of sustainable tourism destinations in many regions around the world. Appreciation of order and architectural beauty is an old approach that needs to be re-actualized in the context of developing an integrated tourism component based on local competencies. Qualitative research with a phenomenological approach explains the noumena (meaning) behind the phenomena (facts) regarding order and the beauty of natural and artificial socio-technical architecture in tourism destinations in Tana Toraja Indonesia. The results of the study found that there are works of natural architecture that are orderly (ordered) and beautiful and have symbolic meaning as a result of the creation of God Almighty so that they are used as preconditions or the basis for the competitiveness of tourism destinations in Tana Toraja. Appreciation and articulation of basic values and noumena value orientations behind natural and artificial architectural phenomena are reflected in the order and beauty of nature and the environment of the tourism destinations being studied. Order and the beauty of natural and artificial architecture are the results of the creation of God Almighty as a comparative advantage and the result of the creativity and innovation of local community members with added value as a precondition or basis for the competitiveness of sustainable tourism destinations.